On Properties of the Phase-type Mixed Poisson Process and its Applications to Reliability Shock Modeling - Goyal, Dheeraj; Hazra, Nil Kamal; Finkelstein, Maxim (Methodology and computing in applied probability, 2022)
Although Poisson processes are widely used in various applications for modeling of recurrent point events, there exist obvious limitations. Several specific mixed Poisson processes (which are formally not Poisson processes any more) that were recently introduced in the literature overcome some of these limitations. In this paper, we define a general mixed Poisson process with the phase-type (PH) distribution as the mixing one. As the PH distribution is dense in the set of lifetime distributions, the new process can be used to approximate any mixed Poisson process. We study some basic stochastic properties of the new process and discuss relevant applications by considering the extreme shock model, the stochastic failure rate model and the δ -shock model.